Peran Akuntansi Dalam Mewujudkan Good Governance: (Studi Kasus Pada Dinas Sosial Provinsi Sumatera Utara) - Muhammad Yafizham; Aqwa Naser Daulay (BADAN PENERBIT STIEPARI PRESS, 2024)
Accountability and transparency, which are the embodiment of good governance practices (good governance/GG) in the financial management of central and regional governments as public sector organizations, are important goals of public sector accounting and administration reform. This research aims to determine the role of accounting in realizing good governance. This type of research is qualitative research, which is carried out using two types of data, namely primary data and secondary data. The results of the research show that the role of accounting in realizing accountability in the North Sumatra Social Service is very important, and overall the North Sumatra Social Service has implemented the principles of good governance in public sector organizations by involving accounting in it. The principles of accountability, responsibility, transparency, efficiency and effectiveness, as well as the strategic vision and mission of the North Sumatra Social Service can be realized with the role of accounting, because accounting is very important and sustainable in presenting, reporting and being accountable for public sector performance reports in accordance with the principles of financial reporting accrual basis based on applicable regulations.